A new deep-sea pectinid bivalve from thermal vents of Manus back-arc Basin (south-western Pacific), Sinepecten segonzaci n. gen., n. sp. (Pectinoidea: Pectinidae), and its relationships with the genera Bathypecten and Catillopecten - Schein, Elisabeth (Zootaxa, 2006)
Sinepecten segonzaci new genus and new species is described from a thermal vent environment in the Manus back-arc basin, North of New Guinea (south-western Pacific) at 1620–1680 m depth. Sinepecten segonzaci has close affinities with species of the genera Bathypecten and Catillopecten. It differs from the living fossil B. vulcani Schein-Fatton, 1985 from hydrothermal vents of the East Pacific Rise (13°N, 2630 m) in its ornamentation and in two main derived characters of the right valve: a prismatic shell microstructure is restricted to the juvenile stage and there is a specialized byssal notch in the new genus and species. Characters, shell ontogeny and biogeography of the three genera Bathypecten, Catillopecten and Sinepecten are compared to discuss their place in pectinid evolution.Keys words: Sinepecten segonzaci, new taxa, ontogeny, hydrothermal vents, back-arc basin, Western Pacific, Bivalvia, Pectinidae